Integrating learner needs into ESP curriculum development: A comprehensive approach to syllabus design and adaptation - Petro, Jonida; Cenaj, Mirjeta; Kushta, Entela; Brahja, Anjeza (Edelweiss Applied Science and Technology, 2025)
Development of ESP courses—including curriculum planning, resource selection, teaching methods, assessment, and evaluation—is typically guided by an analysis of students’ needs. This study aims to identify the English language requirements of students, with particular attention to specific language skills and their integration into ESP syllabus development. It explores both linguistic competencies and related non-linguistic needs. Employing a mixed-methods design, the study collected data via an online survey administered to 140 first-year students during the 2022–2023 academic year. The findings show that although most students recognize the value of English proficiency for their studies, a notable proportion remain unsure of its importance. Writing and listening emerged as the most demanding skills according to students, followed by speaking and reading, indicating critical areas for targeted improvement. Furthermore, while many students foresee needing English for future academic or professional endeavors, a significant number are uncertain about its long-term relevance. These results highlight the necessity of designing an ESP syllabus that strengthens essential language skills while aligning with students’ academic goals and career aspirations. Addressing these language needs can enhance students’ access to knowledge and professional growth, which are vital for sustainable development and global engagement.